A Política Indigenista na Imprensa Goiana: A Visão do Jornal Goyaz: Órgão Democrata (1885-1910). 2023 - ALVES, Ana Tássia Carneiro (Universidade Federal do Tocantins, 2024)
In the present work we present the results of the investigation on the project of compulsory social insertion of the indigenous people, as foreseen by the Brazilian indigenist policy since the Colonial Period. To carry out the research, we took as a source of analysis the newspaper Goyaz: organ democrata, which circulated, regionally, between the years 1885 to 1910, and the bibliography that deals with the indigenous people in Brazil and Goiás. When analyzing the place of the subjects' speech in the newspaper, we take as a basis the statement by Pierre Bourdieu (2005, p. 24-25), according to which language reveals the position of the utterance in the "social hierarchy", including historical aspects in this economic and symbolic. His statement is interesting because the researched newspaper is owned by the Bulhões family, who traditionally belonged to the political elite of Goiás. Through the analysis of articles in the newspaper Goyaz: Organ Democrata, we note that the proposal for the compulsory inclusion of indigenous people involved carrying out catechism and using them as labor, in order to carry out a civilization” (modification) of customs of the original peoples, with a view to following the standards of white and European society. Foreign missionaries were, for a long time, responsible for the indigenist policy in Brazil and this had negative impacts, as it contributed to the realization, in addition to the physical violence caused by the invaders, a symbolic violence by the imposition of new customs and worldviews of capitalist society